Age‐dependency of total tau in the cerebrospinal fluid is corrected by amyloid‐beta 1‐40: A correlational study in healthy adults. (31st December 2021) - Zebhauser, Paul Theo; Berthele, Achim; Franz, Marie‐Sophie; Goldhardt, Oliver; Diehl‐Schmid, Janine; Priller, Josef; Ortner, Marion; Grimmer, Timo
Abstract: Background: Tau‐proteins are established biomarkers of neuroaxonal damage in a wide range of neurodegenerative conditions. Although measurement of total‐Tau (t‐Tau) in the cerebrospinal fluid (CSF) is widely used in research and clinical settings, the relationship of age and t‐Tau in the CSF is not yet fully understood. While a small number of studies reported a correlation between age and t‐Tau in the CSF of healthy adults, in clinical practice the same cut‐off‐value is used independently of patient's age. Method: To further explore the relationship between age and t‐Tau in the CSF and to disentangle neurodegenerative from drainage‐dependent effects in normal aging, we analyzed CSF‐samples of 83 carefully selected cognitively healthy adults and included amyloid‐beta 1‐40 (Aβ40) as a putative marker of drainage from the brain's interstitial system in our analyses. Result: We found a significant correlation of t‐Tau and age, which was no longer present when correcting t‐Tau‐ for Aβ40‐concentrations. Conclusion: These findings were replicated under varied inclusion criteria and call into question the reported association of age and t‐Tau in the CSF. Furthermore, they suggest diagnostic utility of Aβ40 as a possible proxy for drainage‐mechanisms of peptides into the CSF when interpreting biomarker concentrations in the context of neurodegenerative disease.